2016
DOI: 10.1111/aos.13085
|View full text |Cite
|
Sign up to set email alerts
|

Ocular morphology and visual function in relation to general growth in moderate‐to‐late preterm school‐aged children

Abstract: Macular volume was significantly less in MLP children than in controls examined at 8 years of age. General growth of children and IGF-I levels seem to be involved in development of ocular growth and morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
4
14
0
Order By: Relevance
“…Statistically significant thickening was noted in the foveal minimum and central retinal thickness of LE, though ff-ERG was unfortunately performed only on RE which might explain the possibility of missing mild cone dysfunction. Similar to our previous findings in the same cohort of MLP children examined at 8 years of age, central retinal thickness was still thicker in the MLP subset of children than in the controls, although non-significantly so 12. Fulton et al 9 have postulated that former preterm subjects with mild untreated ROP may display minimal cone dysfunction compared with more severe affection in more severe/treated ROP.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Statistically significant thickening was noted in the foveal minimum and central retinal thickness of LE, though ff-ERG was unfortunately performed only on RE which might explain the possibility of missing mild cone dysfunction. Similar to our previous findings in the same cohort of MLP children examined at 8 years of age, central retinal thickness was still thicker in the MLP subset of children than in the controls, although non-significantly so 12. Fulton et al 9 have postulated that former preterm subjects with mild untreated ROP may display minimal cone dysfunction compared with more severe affection in more severe/treated ROP.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, as none of the studied children born MLP had or have been treated for ROP, this suggests that immaturity per se might lead to mild morphological changes, as noted by our previous study 12. In addition, lower GA was associated with reduced cone response measured by ff-ERG.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Similar findings were reported by previous studies (Park & Oh 2012;Bowl et al 2016). We found significantly increased thickness of central fovea in preterm ROPtreated children as compared to controls, in agreement with several previous reports (Ecsedy et al 2007;Akerblom et al 2011;Vinekar et al 2011;Bowl et al 2016;Raffa et al 2016). A study from Wang et al (2012) has shown that premature birth is associated with the failure of inner retinal layers to migrate away from the fovea, resulting in increased foveal thickness in patients with ROP, contributing to central photoreceptor compromise in the oxygen-induced retinopathy animal model of ROP (Shao et al 2011).…”
Section: Bcva Logmarsupporting
confidence: 92%
“…Although, the DA and RA were smaller in prematurely born children compared to full-terms, they both decreased with increasing GA. In contrast, Raffa et al (2016) described a positive correlation between DA and BW in their material of moderate-to-late-preterm children. However, a reduction in DA with increasing BW and GA and a reduction in RA with increasing BW were also found by Hellstr€ om and co-authors, when analysing fundus photographs .…”
Section: Discussionmentioning
confidence: 87%